A Chaos-Based Video watermarking in Wavelet Domain - Somayyeh Mohammadi (Ciência e Natura, 2015)
A novel vide o watermarking scheme based on chaotic maps and wavelet transform is proposed in this paper. The algorithm encrypts a logo image as a watermark signal by bit xor’ing the pixel values of logo and a chaotic map, thus the security of the proposed scheme will be increased . In order to enjoy a robust watermarking algorithm, the chaotic watermark signal is embedded into the discrete wavelet transform coefficients of I - frames,. The investigational results demonstrate that the proposed design can achieve outstandin g robustness to common attacks, and it surpasses the existing techniques.